INTENSITY OF FREE-RADICAL PROCESSES AND ANTIOXIDANT SYSTEM ENZYME STRENGTH IN THE SALIVA OF CHILDREN IN A SETTING OF NATURAL IODINE DEFICIENCY MANAGEMENT - A.A. Dzhumagaziev; A.B. Myasishcheva; D.A. Bezrukova (Педиатрическая фармакология, 2009)
The article showcases the efficacy of taking iodine medications during pregnancy and galactosis to prevent iodine deficiency and related complications in newborn infants. Determination of the level of protein oxidation products (derivatives of 2,4-dinitrophenylhydrazine) in saliva based on the study results proved promising as a non-invasive method of diagnosing iodine deficiency conditions. In addition, the authors has demonstrated that the degree to which the level of the stated compounds in saliva is correlated not only with the manifestation of iodine deficiency, but also with the severity of damage to the central nervous system.Key words: iodine deficiency condition, protein fractions of saliva, prevention of iodine.